Tetratricopeptide repeat motifs in the world of bacterial pathogens: role in virulence mechanisms - Cerveny, Lukas; Straskova, Adela; Dankova, Vera; Hartlova, Anetta; Ceckova, Martina; Staud, Frantisek; Stulik, Jiri (Infection and immunity, 2013)
The tetratricopeptide repeat (TPR) structural motif is known to occur in a wide variety of proteins present in prokaryotic and eukaryotic organisms. The TPR motif represents an elegant module for the assembly of various multiprotein complexes, and thus, TPR-containing proteins often play roles in vital cell processes. As the TPR profile is well defined, the complete TPR protein repertoire of a bacterium with a known genomic sequence can be predicted. This provides a tremendous opportunity for investigators to identify new TPR-containing proteins and study them in detail. In the past decade, TPR-containing proteins of bacterial pathogens have been reported to be directly related to virulence-associated functions. In this minireview, we summarize the current knowledge of the TPR-containing proteins involved in virulence mechanisms of bacterial pathogens while highlighting the importance of TPR motifs for the proper functioning of class II chaperones of a type III secretion system in the pathogenesis of Yersinia, Pseudomonas, and Shigella.
Keywords: regulace genové exprese u bakterií; Gene Expression Regulation, Bacterial; Bacterial Proteins; Virulence; Bacteria; Amino Acid Motifs; virulence; bakteriální proteiny; aminokyselinové motivy